Seaweed Oligosaccharides Stimulate Plant Growth by Enhancing Carbon and Nitrogen Assimilation, Basal Metabolism, and Cell Division - Moenne-Munoz, A; Gonzalez-Figueroa, A (2013)
Sin Editorial Disponible